Postoperative Plasma Mitochondrial DNA and Cytokine Profiles of Elderly Patients Undergoing Minimally Invasive Aortic Valve Replacement - Estevez-Cid, Francisco; Serrano-Teruel, Maria E.; Fernandez-Rodriguez, Fernando; Bouzas-Mosquera, Alberto; Fernandez-Moreno, Mercedes; Dieguez-Garcia, Paula; Cuenca-Castillo, Jose J.; Bautista-Hernandez, Victor (The Thoracic and Cardiovascular Surgeon, 2019)
Introduction Mitochondrial DNA (mtDNA) is gaining increasing interest as a marker of cellular damage and could also act as an inflammatory mediator in cardiopulmonary bypass induced postoperative inflammatory response. Although minimally invasive heart valve surgery reportedly reduces inflammation, the mtDNA and cytokine profile in this context remains unclear.Materials and Methods Here, we report a prospective series of 40 elderly patients with aortic stenosis who underwent bioprosthetic aortic valve replacement (AVR) through upper ministernotomy with either a sutureless (n = 20) or a conventional (n = 20) valve. Primary end points included serial plasma levels of mtDNA (T1: at baseline; T2: 4 hours after surgery; and T3: 24s hour after surgery), cytokines (interleukin-6 [IL-6], tumor necrosis factor-α [TNF-α]), and myocardial necrosis biomarkers (MNBs), whereas secondary end points included clinical and echocardiographic data.Results Significant increases in the postoperative plasma levels (T2) of mtDNA, cytokines, and MNBs were observed in all patients. The postoperative plasma levels of mtDNA, TNF-α, and MNBs showed no significant differences between the treatment groups, although there was a trend toward lower levels in the sutureless group. The decreases in aortic cross-clamp and cardiopulmonary bypass times seen in the sutureless group were associated with significant lower postoperative levels (T2 and T3) of IL-6.Conclusion AVR through upper ministernotomy was associated with a significant increase in postoperative plasma levels of mtDNA and cytokines. There was no difference in the mtDNA levels between the sutureless and conventional valve groups, suggesting a similar level of inflammation in both groups. However, the shorter operation time observed in the sutureless valve group was associated with significantly lower postoperative levels of IL-6, indicating potential clinical benefits.
Keywords: aortic valve; minimally invasive surgery; inflammation; systemic; cardiopulmonary bypass; CPB